O real e o ficcional nos saberes vulgares: ensaio sobre as fronteiras e zonas de transparência entre a História e a Literatura: essay on the boundaries and zones of transparency between history and literature (Revista de História da UEG (REVHIST), 2020)
Abstract: This paper aims to discuss approximations and differences between the writing of history and literature. Just as in Antiquity Plato expelled poets of the Republic, modernity dislodged the literature of reality dimension. This event caused it to be engendered under the gaze of Western culture, the image of literature as contrary to all that is true. The characteristic of fiction present in literary texts would then be conceived as synonymous of deception, falsehood, of untruth. Literature would be a mere pastime of idle people. In discussing the boundaries and zones of transparency of history and literature, we are precisely shedding light on what can put in question how this knowledge is socially engendered. What is wanted to know is the way this relationship between history and literature was conceived by Western culture from a diachronic perspective. Thus, we consider here the ability to produce the reality that literature has and the imaginative capacity of which history is nourished. It is then up to us to think the borders and the transparency zones between these two discourses.Keywords: History. Literature. Writing. Fiction. Transparency zones. Borders.